Temporary Extrathoracic Vacuum Therapy Splint in Chest Wall Reconstruction - Srikanth Vasudevan; Shriram Vaidya; Ritu Baath S.; Ashok Basur C.; Anantheswar Yellambalase N.; Sudarshan Reddy Nagireddy (Indian Journal of Plastic Surgery)
Background Paradoxical respiration is a sinister consequence of bony chest cage defects which can persist even post chest wall reconstruction. It leads to prolonged dependence on mechanical ventilation postoperatively, thereby delaying recovery. Methods Negative pressure wound therapy (NPWT) was applied in early postoperative period to a patient with chest wall defect reconstructed with folded prolene mesh and free anterolateral thigh flap. Arterial blood gas (ABG), fraction of inspired oxygen (FiO2), peak end expiratory pressure (PEEP), oxygen saturation (SpO2), and blood pressure (BP) readings pre and post NPWT application were compared. Results There was marked improvement in the breathing mechanics and related parameters post NPWT application over the flap. Conclusions Negative extrathoracic pressure in the form of a temporary splint can enable early weaning off the ventilator and a smoother postoperative recovery in reconstructed chest wall defects.